1995
DOI: 10.1007/bf01987278
|View full text |Cite
|
Sign up to set email alerts
|

The frameless GyneFix® intrauterine implant: A major improvement in efficacy, expulsion and tolerance

Abstract: The CuFix (GyneFix), conceived in 1985, was developed to minimize three major problems frequently associated with discontinuation of IUD use: expulsion, bleeding and pain. Since the initial clinical investigations, over 10,000 woman years of experience and up to 8 years of follow-up in international multicenter, non-comparative and comparative clinical trials, including a large proportion of nulligravid/nulliparous women, have been collected. Based on new clinical information about the GyneFix from a long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…The 3-year expulsion rate in a non-comparative trial involving both nulliparous and parous women was 0.7%. 1 A randomised comparative trial in parous women in China found the expulsion rate with the GyneFix to be significantly lower (3.0%) than that of the framed device, the T380A (7.4%), at 3 years. 4 The authors state that most expulsions with GyneFix occur within 3 months of insertion, representing 'insertion failures' due to insufficient implantation of the anchoring knot into the fundal myometrium through lack of experience with the technique.…”
Section: Introductionmentioning
confidence: 99%
“…The 3-year expulsion rate in a non-comparative trial involving both nulliparous and parous women was 0.7%. 1 A randomised comparative trial in parous women in China found the expulsion rate with the GyneFix to be significantly lower (3.0%) than that of the framed device, the T380A (7.4%), at 3 years. 4 The authors state that most expulsions with GyneFix occur within 3 months of insertion, representing 'insertion failures' due to insufficient implantation of the anchoring knot into the fundal myometrium through lack of experience with the technique.…”
Section: Introductionmentioning
confidence: 99%
“…3 Perforation at insertion, delayed perforation, or migration has not been recorded in large international multicenter clinical trials with the frameless device. 4,5 It might be supposed that a frameless device anchored in the myometrium might erode through more easily than a framed device. The absence in perforation rates may refute this supposition although there may be considerable underreporting.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reasons for discontinuation were expulsion, bleeding and/or pain. 20 The initial trials with the frameless IUD conducted in Belgium, and later internationally, in parous and nulliparous women, were promising 21,22 . However, the WHO randomised clinical trial comparing the TCu380A with the frameless Flexigard 1 IUD (Flexigard 1 , developed by GynoPharma, Inc. in the USA, uses the same frameless design as that of the current GyneFix 1 IUD but a different inserter), involving parous women only, did not show a difference in removal rate for bleeding and pain 23 .…”
Section: F R a M E L E S S I N T R A U T E R I N E C O N T R A C E P mentioning
confidence: 98%